How life circumstances during public health crises affect people to share and correct misinformation: a perspective of the third-person effect - Tian, Xiang (Frontiers in Psychology, 2024)
Introduction: Misinformation spread on social media often parallels with public crises like the outbreak of COVID-19, because people's behaviors on misinformation may be influenced by the typical life circumstance. With the increasing severity of living conditions, misinformation is believed to be more widely spread, and corrective behaviors tend to decrease. Furthermore, social comparison also affects the perception of life circumstance and subsequent behaviors. Taking Shanghai's lockdown for COVID-19 as an example, this study examined whether the two representative factorsthe duration of the lockdown and the satisfaction with relief measuresaffected people to share and correct misinformation. By employing the Third-Person Effect theory, underlying social comparison mechanisms were also explored.Methods: An online survey was conducted in April 2022, when Zero-COVID policy was implemented in Shanghai. Besides questions about the life circumstance, Third-Person Perception scale, behaviors of sharing misinformation scale, and behaviors of correcting misinformation scale were included. Finally, 7962 valid responses were collected.Results: It is found that both behaviorssharing and correcting misinformation -were affected by life circumstance, but in distinct ways. The evidence also supported the existence of Third-Person Perception. The relationship between the satisfaction with relief measures and sharing behavior was shown to be mediated by Third-Person Perception.This study unveils that the proliferation of misinformation during the crises is related to the deterioration of people's perception of life circumstance. Social comparison often plays significant role, reflected as the Third-Person Effect.